Health care safety incidents in paediatric emergency care - Dolores Beteta Fernández; Ana Miriam Seva Llor; Laura Martínez Alarcón; Carlos Pérez Cánovas; Manuel Pardo Ríos; Julián Alcaraz Martínez (Elsevier, 2024)
Objective: To characterize safety incidents in paediatric emergency departments (PEDs): frequency, sources, root causes, and consequences. Materials and methods: We conducted a cross-sectional, observational and descriptive study in the PED of the Clinical University Hospital XX (blinded for review). Patients were recruited through opportunity sampling and the data were collected during care delivery and one week later through a telephone survey. The methodology was based on the ERIDA study on patient safety incidents related to emergency care, which in turn was based on the ENEAS and EVADUR studies. Results: The study included a total of 204 cases. At least one incident was detected in 25 cases, with two incidents detected in 3 cases, for a total incidence of 12.3%. Twelve incidents were detected during care delivery and the rest during the telephone call. Ten percent did not reach the patient, 7.1% reached the patient but caused no harm, and 82.1% reached the patient and caused harm. Thirteen incidents (46.4%) did not have an impact on care delivery, 8 (28.6%) required a new visit or referral, 6 (21.4%) required additional observation and 1 (3.6%) medical or surgical treatment. The most frequent root causes were health care delivery and medication. Incidents related to procedures and medication were most frequent. Of all incidents, 78.6% were considered preventable, with 50% identified as clear failures in health care delivery. Conclusions: Safety incidents affected 12.3% of children managed in the PED of the HCUVA, of which 78.6% were preventable. Resumen: Objetivo: Caracterizar los incidentes de seguridad en los servicios de urgencias pediátricas (SUP): frecuencia, fuentes, factores causales y consecuencias. Material y métodos: Estudio observacional, descriptivo y transversal, en los SUP del Hospital Clínico Universitario XX (cegado para revisión). Aleatorización por oportunidad en turno de mañana, tarde y noche: Se recogieron datos durante la asistencia y una semana después por encuesta telefónica. La metodología se basó en los estudios de incidentes derivados de la atención en urgencias ERIDA, basado a su vez en los estudios ENEAS y EVADUR. Resultados: Se incluyeron 204 casos. En 25 casos se detectó al menos un incidente, 3 casos tuvieron 2, con una tasa total de 12,3%. 12 incidentes se detectaron en la asistencia, resto en la llamada. El 10% no afectaron al paciente, el 7,1% afectaron pero sin daño y 82,1% afectaron con daño. En 13 incidentes (46,4%) la atención no se vio afectada, en 8 (28,6%) precisaron nueva consulta o derivación, en 6 (21,4%) precisaron más observación y en 1 (3,6%) tratamiento médico o quirúrgico. Los factores causales más frecuentes fueron los relacionados con los cuidados y con la medicación. Los efectos derivados de los procedimiento y medicación fueron los más usuales. El 78,6% de los incidentes se consideraron evitables, identificandose el 50% como fallo claro de actuación. Conclusiones: El 12,3% de los niños atendidos en SUP del HCUVA sufrieron un incidente de seguridad, teniendo una evitabilidad del 78,6%.